Obituary: Frank Ainsworth - Leon Fulcher (Scottish Journal of Residential Child Care)
Join me in remembering Frank Ainsworth, whom I met in the early 1970s at a conference in Aberdeen. Frank became one of the first university-based advocate of residential child care and residential social work in Scotland following his appointment as a Lecturer in Residential Child Care and Social Work at the University of Dundee. Entry to university teaching followed a professional journey through adult corrections where Frank was closely engaged in Borstal training and the development of community group homes for young offenders. After Dundee, Frank was appointed to the Central Council for Education and Training in Social Work (CCETSW) as UK advisor on residential care practice as part of social work. In this role Frank advanced the transition of specialist courses in residential care into mainstream social work education.